Biomarkers of environmental manganese exposure. (21st April 2022) - Shilnikova, Natalia; Karyakina, Nataliya; Farhat, Nawal; Ramoju, Siva; Cline, Brandon; Momoli, Franco; Mattison, Donald; Jensen, Natalie; Terrell, Rowan; Krewski, Daniel
Abstract: We conducted a critical review on biomarkers of environmental manganese (Mn) exposure to answer the following questions: 1) are there reliable biomarkers of internal Mn exposure (Mn in biological matrices) associated with external metrics of Mn exposure (Mn in environmental media)? and 2) are there accurate reference values (RVs) for Mn in biological matrices? Three bibliographic databases were searched for relevant references and identified references were screened by two independent reviewers. Of the 6342 unique references identified, 86 articles were retained for data abstraction. Our analysis of currently available evidence suggests that Mn levels in blood and urine are not useful biomarkers of Mn exposure in non-occupational settings. The strength of the association between Mn in environmental media and saliva was variable. Findings regarding the utility of hair Mn as a biomarker of environmental Mn exposure are inconsistent. Measurements of Mn in teeth are technically challenging and findings on Mn in tooth components are scarce. In non-occupationally exposed individuals, bone Mn measurements using in vivo neutron activation analysis (IVNAA) are associated with large uncertainties. Findings suggest that Mn in nails may reflect Mn in environmental media and discriminate between groups of individuals exposed to different environmental Mn levels, although more research is needed. Currently, there is no strong evidence for any biological matrix as a valid biomarker of Mn exposure in non-occupational settings. Because of methodological limitations in studies aimed at derivation of RVs for Mn in biological materials, accurate RVs are scarce.